Effects of the routine multiple vaccinations on the expression of innate immune molecules and induction of histone modification in ovarian cells of layer chicks. (19th April 2019) - Kang, Y; Nii, T; Isobe, N; Yoshimura, Y
ABSTRACT: The aim of this study was to determine whether vaccination affects the expression of Toll-like receptors (TLRs ), cytokines, and avian β-defensins (AvBDs ) in the chick ovary with or without lipopolysaccharide (LPS ) stimulation. White Leghorn female chicks were administered vaccines for infectious bronchitis, Marek's disease, Newcastle disease, and infectious bursal disease during the first 14 D after hatching and ovarian tissues were collected on day 21. Control chicks received water or dilution buffer in place of vaccine. In Experiment 1, ovarian tissues were incubated with or without LPS, and the expression of innate immune molecules (TLRs, cytokines, and AvBDs) was examined by real-time PCR. In Experiment 2, the levels of histone modification in fresh ovarian tissues were examined by western blot analysis. The results of Experiment 1 showed that, in vaccinated chick ovaries, the expression of TLR1-1, 2-1, 2-2, and 21 was up-regulated, whereas that of TLR1-2, 4, and 7 was down-regulated under LPS stimulation. Among the examined 6 cytokines, only the expression of TNFSF15 was lower in the ovaries of vaccinated chicks than that in control with or without LPS stimulation. The expression of AvBD1, 2, 4, and 7 was lower in the ovaries of vaccinated chicks than in control without LPS stimulation, and that of AvBD1 and 2 was also lower even in ovaries incubated with LPS. In Experiment 2, the density of di-methyl histone H3 (Lys9) and acetyl histone H3 (Lys9) was significantly higher in the vaccine group than in the control, whereas di-methyl and tri-methyl histone H3 (Lys4) and acetyl histone H3 (Lys27) did not show differences between the groups. These results suggest that vaccination positively or negatively affects the expression of innate immune molecules in the chick ovary including TLRs, TNFSF15, and AvBDs, and it may be associated with epigenetic reprogramming by histone modifications in ovarian cells. Thus, in the future, it may be possible to develop or improve vaccination programs for the enhancement of the innate immune system in the hen ovary.